Pelatihan Penulisan Artikel di Jurnal Nasional Terakreditasi dan Internasional Bereputasi Bagi Mahasiswa Magister Pendidikan IPA Universitas Mataram - Aris Doyan; Susilawati Susilawati; Ahmad Harjono (Pascasarjana Universitas Mataram, 2021)
Article writing training in accredited and internationally reputable national journals for master of science education students has been conducted online using zoom meetings. This training activity aims to train master of science education students to be able to publish work from their research results in accredited national journals and in reputable journals indexed scopus. The event was attended by 16 students during seven zoom meeting meetings and using WhatApp group. The results of this journal surgery show that students have been able to submit, review and repair and publish their articles in the journal jppipa.unram.ac.id